Pengaruh Pendekatan Steam Terhadap Kreativitas dan Hasil Belajar Matematika Siswa SD - Rekha Herlina Putri; Melva Zainil; Salmaini Salmaini; Adrias Adrias (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study aims to examine the effect of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach on students’ creativity and mathematics learning outcomes in elementary school. This research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The subjects of this study were fifth-grade students, consisting of an experimental class and a control class. The experimental class received mathematics learning using the STEAM approach, while the control class received conventional learning. Data were collected through creativity observation sheets and mathematics learning outcome tests administered in pretest and posttest. The data were analyzed using descriptive and inferential statistics, including normality tests, homogeneity tests, and multivariate hypothesis testing. The results showed that there were significant differences between the experimental and control classes in terms of students’ creativity and mathematics learning outcomes. The experimental class demonstrated higher improvement and more homogeneous learning outcomes compared to the control class. These findings indicate that the STEAM approach is effective in enhancing students’ creativity and mathematics learning outcomes, particularly in geometry topics. Therefore, the STEAM approach can be recommended as an innovative and effective learning strategy in elementary mathematics education.